Innovative Closely Spaced Profiling and Current Velocity Measurements in the Southern Baltic Sea in 2016–2018 With Special Reference to the Bottom Layer - Paka, Vadim T.; Zhurbas, Victor M.; Golenko, Maria N.; Korzh, Andrey O.; Kondrashov, Alexey A.; Shchuka, Sergey A. (Frontiers in Earth Science, 2019)
A solution of the problem of determination of spatial variability of oceanographic fields with a fine structure resolution higher than it was possible previously using towed scanning probes was presented for the Baltic Sea. Another concurrently solved problem consists in obtaining data on the structure of waters in the bottom layer, which was difficult to implement by application of previous methods. Instead of scanning along inclined paths, a new measurement technique allows for a quasi-free probe drop with a constant sink rate and with reaching the bottom at each dive cycle along the route of the ship independent of the pitch of the ship and optimal for the applied probe. The new measurement technique is simpler and more efficient than the previous one. In addition, the problem of measuring velocity of both very weak and strong currents in a thin bottom layer, including stagnant zones, slopes, sills and underwater channels, was suggested to be solved using clusters consisting of a sufficiently large number of autonomous Tilt Current Meters (TCM) of original design. The innovation benefits are illustrated on the results of a monitoring campaign that was carried out in the southern Baltic Sea in 2016-2018. Among the new findings there are the highest ever recorded temperature, 14.3 °C, in the halocline of the Bornholm Basin measured after a baroclinic inflow event in early Autumn 2018, and an extraordinarily large current velocity of saltwater flow of more than 0.5 m/s, recorded by a TCM within a 1 m thick bottom layer at the eastern slope of the Hoburg Channel during a period when the northwesterly wind had intensified to severe gale.